Fake News and Populism: New Threats to Public Trust - Pira, Francesco; Casagrande, Roberta (SocietàMutamentoPolitica, 2024)
The article analyses the growing distrust of cultural intermediaries and social and political actors, fuelled by phenomena such as fake news, disinformation and denialism. Indeed, post-modernity has eroded trust in traditional media, facilitating the dissemination of unverified information and making it difficult to discern between reliable and unreliable sources. Events such as the Covid-19 pandemic and the Russia-Ukraine conflict highlight how communication strategies can profoundly influence public perception. In this context, populism exploits simplifications and emotionally charged narratives, promoting alternative versions of truth that challenge official narratives and contribute to a further polarization of society.